2012
DOI: 10.1016/j.freeradbiomed.2012.05.043
|View full text |Cite
|
Sign up to set email alerts
|

Cimicifuga racemosa impairs fatty acid β-oxidation and induces oxidative stress in livers of ovariectomized rats with renovascular hypertension

Abstract: The aim of this work was to evaluate the effects of therapeutic doses of Cimicifuga racemosa on cardiovascular parameters and on liver lipid metabolism and redox status in an animal model of estrogen deficiency associated with hypertension, a condition that could make the liver more vulnerable to drug-induced injuries. Female Wistar rats were subjected to the surgical procedures of bilateral ovariectomy (OVX) and induction of renovascular hypertension (two-kidneys, one-clip; 2K1C). These animals (OVX + 2K1C) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
31
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 58 publications
12
31
0
Order By: Relevance
“…This organ is a frequent target of drug action, and drug-induced hepatotoxicity (drug-induced liver injury or DILI) is a common cause of liver failure and withdrawal of drugs (Labbe et al, 2008). Many substances produce hepatotoxicity by directly or indirectly inducing oxidative stress (Berson et al, 1998;Campos et al, 2012;Fromenty and Pessayre, 1995;Labbe et al, 2008). The evaluation of the liver of the females, however, showed that the extract did not produce changes in the redox state of this organ.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This organ is a frequent target of drug action, and drug-induced hepatotoxicity (drug-induced liver injury or DILI) is a common cause of liver failure and withdrawal of drugs (Labbe et al, 2008). Many substances produce hepatotoxicity by directly or indirectly inducing oxidative stress (Berson et al, 1998;Campos et al, 2012;Fromenty and Pessayre, 1995;Labbe et al, 2008). The evaluation of the liver of the females, however, showed that the extract did not produce changes in the redox state of this organ.…”
Section: Discussionmentioning
confidence: 99%
“…The content of reduced glutathione (GSH) was analyzed in the supernatant, using o-phthalaldehyde (OPT) as a fluorescent probe in a spectrofluorimeter (excitation 350 nm, emission 420 nm) (Campos et al, 2012;Hissin and Hilf, 1976) and used as an indicator of the redox state of the liver.…”
Section: Evaluation Of the Redox State Of The Livermentioning
confidence: 99%
See 2 more Smart Citations
“…CR impairs fatty acid b-oxidation and induces oxidative stress in livers of ovariectomized rats with renovascular hypertension (Campos et al, 2012). Quality problems in a few CR products were evident that require additional regulatory quality specifications (Teschke et al, 2011).…”
Section: Adverse Effects and Safetymentioning
confidence: 99%